Constraints on Ceres' Internal Structure and Evolution From Its Shape and Gravity Measured by the Dawn Spacecraft. Issue 11 (11th November 2017) - Ermakov, A. I.; Fu, R. R.; Castillo‐Rogez, J. C.; Raymond, C. A.; Park, R. S.; Preusker, F.; Russell, C. T.; Smith, D. E.; Zuber, M. T.
Abstract: Ceres is the largest body in the asteroid belt with a radius of approximately 470 km. In part due to its large mass, Ceres more closely approaches hydrostatic equilibrium than major asteroids. Pre‐Dawn mission shape observations of Ceres revealed a shape consistent with a hydrostatic ellipsoid of revolution. The Dawn spacecraft Framing Camera has been imaging Ceres since March 2015, which has led to high‐resolution shape models of the dwarf planet, while the gravity field has been globally determined to a spherical harmonic degree 14 (equivalent to a spatial wavelength of 211 km) and locally to 18 (a wavelength of 164 km). We use these shape and gravity models to constrain Ceres' internal structure. We find a negative correlation and admittance between topography and gravity at degree 2 and order 2. Low admittances between spherical harmonic degrees 3 and 16 are well explained by Airy isostatic compensation mechanism. Different models of isostasy give crustal densities between 1, 200 and 1, 400 kg/m 3 with our preferred model giving a crustal density of 1, 28 7 + 70 − 87  kg/m 3 . The mantle density is constrained to be 2, 43 4 + 5 − 8  kg/m 3 . We compute isostatic gravity anomaly and find evidence for mascon‐like structures in the two biggest basins. The topographic power spectrum of Ceres and its latitude dependence suggest that viscous relaxation occurred at the long wavelengths (>246 km). Our density constraints combined with finite element modeling of viscous relaxation suggests that the rheology and density of the shallow surface are most consistent with a rock, ice, salt and clathrate mixture. Plain Language Summary: Ceres is the largest body in the asteroid belt. Unlike most of the objects in that region of the solar system, Ceres has a round shape due to its sufficient gravity. Little was known about Ceres before the Dawn mission. The measurements by the Dawn spacecraft allowed precise determination of Ceres' shape and gravity field. We use these two data sets to understand its internal structure. It was predicted in the past that Ceres topography would quickly viscously relax if Ceres had an icy crust. We find only a modest evidence of viscous relaxation, which implies that Ceres' crust is much stronger than water ice. We also find that Ceres topography is isostatically compensated. That is, much like with a floating iceberg, the weight of mountains is compensated by a displaced volume of the underlying mantle. Such a simple model explains most of Ceres' gravity anomalies. However, some gravity anomalies remain unaccounted for. For example, we find evidence for a mass concentration analogous to those in lunar maria in the two biggest impact basins. A strong negative anomaly is observed around Occator—the famous bright spot crater. A strong positive anomaly is centered at Ahuna Mons—a unique pyramid‐shaped mountain. The globally averaged crustal density that we find is rather low. Remarkably, Ceres crust is made out of a strong, rock‐like material that, however, has a density much lower than that of rocks. This implies that Ceres' crust contains a lot of salts and clathrates, which are strong and light materials. Key Points: We use a two‐layer isostatic model to derive constraints on Ceres' internal structure Deviation of topography power spectrum from a power law and more subdued topography at equator are indicative of limited viscous relaxation Observed isostatic anomalies include mascon‐like structures in big impact basins and strong gravity anomalies at Occator and Ahuna Mons